2016
DOI: 10.3390/ijerph13020185
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between AMH and AMHR2 Polymorphisms and the Follicular Phase in Late Reproductive Stage Women

Abstract: The objective of this work was the analysis of the relationships between the genotypes of the AMH and AMH receptor type 2 genes, hormone levels and the menstrual cycle in a group of Polish women in the late reproductive stage. The study was conducted using a measurement-based method (body weight and height), laboratory method (serum hormone levels AMH, FSH and E2), and genetic analysis (DNA isolated from whole blood by a salting-out method). The study involved 345 healthy, late-reproductive-stage women from Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The European subgroup (Cerra et al, 2016;Jurczak et al, 2016;Kevenaar et al, 2007bKevenaar et al, , 2008 showed a similar result (WMD 0.09, 95% CI −0.43 to 0.62, I 2 = 42.0%). Subgroup analysis in accordance with population showed no significant statistical association in healthy women (Jurczak et al, 2016;Kevenaar et al, 2007b;Yu et al, 2016), infertile women (Cerra et al, 2016;Peluso et al, 2015,) or patients with PCOS (Kevenaar et al, 2008) (WMD 0.66, 95% CI −0.56 to 1.87, I 2 = 75.2%, P = 0.018; WMD 0.47, 95% CI −0.07 to 1.02, I 2 = 0.0%; WMD 0.50, 95% CI −2.19 to 1.19) (FIGURE 2B). However, for PCOS there was only one study for analysis.…”
Section: Ovarian Reservementioning
confidence: 73%
See 3 more Smart Citations
“…The European subgroup (Cerra et al, 2016;Jurczak et al, 2016;Kevenaar et al, 2007bKevenaar et al, , 2008 showed a similar result (WMD 0.09, 95% CI −0.43 to 0.62, I 2 = 42.0%). Subgroup analysis in accordance with population showed no significant statistical association in healthy women (Jurczak et al, 2016;Kevenaar et al, 2007b;Yu et al, 2016), infertile women (Cerra et al, 2016;Peluso et al, 2015,) or patients with PCOS (Kevenaar et al, 2008) (WMD 0.66, 95% CI −0.56 to 1.87, I 2 = 75.2%, P = 0.018; WMD 0.47, 95% CI −0.07 to 1.02, I 2 = 0.0%; WMD 0.50, 95% CI −2.19 to 1.19) (FIGURE 2B). However, for PCOS there was only one study for analysis.…”
Section: Ovarian Reservementioning
confidence: 73%
“…The remaining 35 studies were screened for eligibility and 17 were excluded according to eligibility criteria. Finally, eight studies involving 3155 participants were included in the meta-analysis (Cerra et al, 2016;Georgopoulos et al, 2013;Jurczak et al, 2016;Kevenaar et al, 2007bKevenaar et al, , 2008Lazaros et al, 2016;Peluso et al, 2015, Yu et al 2016. Ten studies were included in the descriptive review (Alvaro Mercadal et al, 2015;Boudjenah et al, 2012;Braem et al, 2013;Hanevik et al, 2010;Karagiorga et al, 2015;Kevenaar et al, 2007a;Qin et al, 2014;Voorhuis et al, 2011;Wang et al, 2002;Yoon et al, 2013).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been numerous studies to date showing differences in ovarian reserve testing parameters as well as number and quality of oocytes in women with polymorphisms of the AMH and AMHR2 genes (100-103). However, others have not found differences in age at natural menopause, prevalence of POI, and ART outcomes in women with and without these polymorphisms (104)(105)(106)(107)(108)(109). In a meta-analysis by Pabalan et al (97) performed in 2016, the associations of the AMH Ile49Ser variant and AMHR2 482A>G variant on reproductive outcomes initially appeared null, however, after subgroup analysis, pooled effects were found in differing ethnic groups with polymorphisms appearing to be protective in whites and variable in those of Asian descent.…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%